1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Dummy Variables in Taylor Series

  1. Apr 12, 2004 #1
    Taylor Series in x-a


    I've got a question about the use of dummy variables in Taylor Series.

    We are asked to expand:

    g(x) = xlnx

    In terms of (x-2). So originally, I used a dummy variable approach to try and find an answer.

    Let t = x-2, so x = t+2.

    g(x) = (t+2)ln(2+t)

    We're given:

    [tex]ln(1+x) = \sum_{k=1}^{\infty}\frac{(-1)^k}{k}x^k[/tex]

    So, I re-arrange g(x) = (t+2)ln[2(1+t/2)] = (t+2)(ln2 + ln(1+t/2)).

    Expanding, I get: g(x) = tln2 + tln(1+t/2) + 2ln2 + 2ln(1+t/2).

    So [tex]g(x) = 2ln2 + (x-2)ln2 + (x-2)\sum_{k=1}^{\infty}\frac{(-1)^k}{k}(x/2-1)^k + [/tex][tex]2\sum_{k=1}^{\infty}\frac{(-1)^k}{k}(x/2-1)^k.[/tex]

    This is where I get stuck because the book's answer says it should be:

    [tex]g(x) = 2ln2 + (1+ln2)(x-2) + \sum_{k=2}^{\infty}\frac{(-1)^k}{k(k-1)2^{k-1}}(x-2)^k[/tex]

    I'm sort of close to the answer, but can't quite make the final manipulations to make it work. The book used the method of taking successive derivatives to arrive at that formula, so I know how to do it that way - but is my original method correct as well? If not, why not?
    Last edited: Apr 12, 2004
  2. jcsd
  3. Apr 12, 2004 #2
    Your method should work out.

    Before we work too much on it, why don't you try putting the two sums you have into one and see if it doesn't match up then?

Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Similar Discussions: Dummy Variables in Taylor Series
  1. Taylor Series (Replies: 3)

  2. Taylor series (Replies: 3)

  3. Taylor series (Replies: 2)

  4. Taylor's Series (Replies: 57)

  5. Taylor series (Replies: 1)